2002
DOI: 10.1177/0165551024234011
|View full text |Cite
|
Sign up to set email alerts
|

Thesaurus-enhanced search interfaces

Abstract: User interfaces to information retrieval systems play a major role in assisting users to search, browse and retrieve information relevant to their needs. This paper provides a review of a category of information retrieval interfaces that are enhanced by incorporating standard thesauri as part of their searching and browsing facilities. A brief account of the rationale behind the integration of thesauri as search aids in such interfaces is provided, based on research literature related to information searching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Hierarchies have been used to support the user in a number of information retrieval tasks, including complex search tasks (Singer et al 2012), collection browsing (Milne et al 2007;Shiri et al 2002), and hierarchical search facets (Hearst 2006a;Stoica et al 2007). In this paper we focus on four key activities that hierarchies support:…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchies have been used to support the user in a number of information retrieval tasks, including complex search tasks (Singer et al 2012), collection browsing (Milne et al 2007;Shiri et al 2002), and hierarchical search facets (Hearst 2006a;Stoica et al 2007). In this paper we focus on four key activities that hierarchies support:…”
Section: Related Workmentioning
confidence: 99%
“…This is particularly relevant to digital libraries where rich user/information interaction is common and requires alternative methods to support users (Rao et al 1995). The provision of browsing functionalities through thesaurus-based search enhancements (Milne et al 2007;Shiri et al 2002), document clustering (Pirolli et al 1996) or the use of concepts arranged hierarchically in facets (Hearst 2006a;Stoica et al 2007) have all been shown to improve the search experience.…”
mentioning
confidence: 99%
“…For instance, the terms entered by the user may be mapped to terms in the thesaurus [32][33][34][35][36]. Some approaches, such as the Automatic Term Mapping (ATM) feature in PubMed, rely on performing the mapping step behind the scenes [37][38][39][40][41][42][43][44].…”
Section: Query Expansionmentioning
confidence: 99%
“…For example, when users do not have clearly defined information needs [36]; when users have complex search tasks [33]; or when they want to gain an overview over a collection [15]. This has led to the design of browsing and exploration functionalities, including thesaurus-based search improvements [23,31], document clustering [27] or the use of concepts arranged hierarchically in facets [12,34]. All approaches have been shown to improve the user's search experience for exploration activities.…”
Section: Introductionmentioning
confidence: 99%